The Ego-States of the Individual Internet- Dependent Adolescents - Aslanyan, Tetyana Sergeevna (Psychological Prospects Journal, 2012)
The article investigates the problem of Internet addiction, considering the paradigm of transactional analysis. The structural and functional analysis of the ego states of personality of Internet-dependent adolescents is realized.